Studi Karakter Peduli Lingkungan Pantai Di Desa Tepi Laut Kabupaten Bengkulu Utara - Nofirman Nofirman (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2018)
Optimal management of natural resources occurs in the form of human interaction with natural resources, the economic result can be a particular commodity. Quality commodities are formed through the hard work of the community that is characterized by its adherence to knowledge, attitudes, skills, and behaviors, so that the goods can have geographical indications. Geographically indicated commodities are formed through a variety of character pemangkunya not least the character of social care and environmental care characters. research was conducted with qualitative approach based on descriptive research method. The results showed that the social care character associated with; faithful behavior, tolerance for differences, friendly behavior, polite behavior, listening behavior, information exchange behavior, caring behavior of community activities, behavior of not taking advantage of others , behavior does not hurt people, and helpful behavior has occurred in the community environment in accordance with the rules and customs of Rejang. There is a difficulty in elaborating the social caring character in the process, thus indicating a latent character. Character cares about coastal environment; the phenomenon of hydro-oceanography, resources can be recovered, resources can not be recovered, environmental services, spatial, disaster mitigation was felt with the condition received less attention from the community. Communities are unaware of coastal conditions, have no capabilities and tools, including no effort to relate to beaches and the sea. The pessimist seeks on the beach because the income they earn can not meet the needs of everyday life, so no commodities or services are geographically indicated.